Design Thinking como Metodologia para Definição da Interface Gráfica de Usuário - Nunes, Daila Rita Becker; Guerra, Luciéli Tolfo Beque; Correa, Claiton (Anais do Encontro Nacional de Computação dos Institutos Federais (ENCompIF), 2020)
Design Thinking has been gaining attention in recent years as a methodology for creating innovative and creative solutions. We can use it to develop solutions for different areas of knowledge. This article addresses the use of Design Thinking as a methodology to support the development of the user interface of the Cine Web 2.0 project, concerning the inside-out approach of development from HCI research field. The article also presents and briefly discusses the results obtained in the project.